Fitness Level Differences between Students in Kosovo and Montenegro - Besnik Morina; Florian Miftari; Dana Badau (MDPI AG, 2021)
Geographical, cultural, and socio-economic factors create a different lifestyle. Accordingly, the aim of this research was to identify the differences in anthropometric and fitness characteristics among adolescents living in Montenegro and Kosovo in order to optimize the physical fitness as a consequence of the proactive behavior. Anthropometric characteristics and fitness level measures were assessed by Eurofit testing battery among 600 Kosovar and 600 Montenegrin students, equally distributed by gender. Differences between countries, gender, and age group (13, 14 and 15 years) were assessed with multivariate and univariate analysis of variance. The results showed that Montenegrin students are taller, heavier, and achieve better results in the sit-ups and 20-m endurance shuttle-run tests. Kosovar students achieve better results in the standing broad jump and 10 × 5 m shuttle-run tests. Males achieve significantly better results in all tests, excluding the sit-and-reach test. Statistically significant differences among age groups were found for all variables, regardless gender and country (except for the flamingo and sit-and reach tests). This study is of importance to physical education teachers and curriculum authors to optimize students' proactive behavior based on the identified anthropometric and physical fitness differences between the two countries, age groups, and genders.